Net maar diere? ’n Tematiese oorsig van die plek van die diereryk in die skepping volgens geselekteerde Skrifgedeeltes - Du Preez, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
A thematic survey of the place of the animal kingdom in God’s world according to some Scripture passages In a time of growing ecological awareness it may prove valuable to trace the place which the animal kingdom according to the Scriptures takes in God’s world. The relevant material unfolds as follows: Every animal unique; The Creator’s compassion on animals; Animals as examples to humans; Animal images for God; Animal images for God’s people; The messianic kingdom sketched by way of animal images; The significance of animal sacrifices in salvation history; Animal service during Jesus’ earthly ministry; The “Prayer relationship” between Creator and animals. As God’s image bearers, who have been appointed to rule over the animal world (Gen. 1: 27-28), it is our duty and privilege to behave in such a way towards them that they will thereby be better enabled to fulfil the significance of their existence in God’s world.